Procesional “trespassers”: Non-mormative iconographies in spanish Holy Week in the early modern - Sánchez Guzmán, Rubén; Fernández Paradas, Antonio Rafael (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this article we will study the presence of those hagiographic images whose iconography places them outside of the Cycle of the Passion of Christ, in Spanish penitential processions throughout history. We will take a closer look at the ones that preside on a processional float alone by its own merits.